AKIBAT HUKUM PERKAWINAN BERBEDA AGAMA DITINJAU DARI UNDANG-UNDANG NOMOR 1 TAHUN 1974 TENTANG PERKAWINAN - Herdiani Syahputri, Cyntia; Astariyani, Ni Luh Gede (Kertha Semaya : Journal Ilmu Hukum, 2014)
The writing is titled "Due Marriage Law Seen From Different Religions Act No. 1 of 1974" which aims to discuss the legal consequences of marriage as where different religions in Indonesia. In this study, using a normative research methods in the solution through a review of the rules - the rules that exist and examines various aspects of the written law. This paper describes the legal consequences perbdaan religion in the Marriage Act. Kesimpualn perkawianan that can pull in different religions have in langsungkan in society is not valid because the intent to deviate from the provisions of article 2, paragraph (1) and Article 8, paragraph (f) of the Marriage Law.
Keywords: Marriage , Different Religions , Legal Due